Pelatihan Pembuatan Video sebagai Media Promosi Dusun - Saputri, Nur Amala (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
One of the most accessible options for the public to build a digital ecosystem is to use social media in communication and socializing practices. This community service activity basically aims to provide training on making village promotional videos for youth groups in Dusun Demen, Pakembinangun, Pakem, Sleman, Yogyakarta, aged 16-20 years. Involving young people as participants in this video training activity is an urgency that is expected to represent Gen Z as active users of the YouTube networking media. The result of this activity is to make young people understand more about the function of social networking media, especially Youtube as a promotional medium. Almost all of the participants became more knowledgeable about procedures and implementing the basic techniques of making videos. They also gain experience and skills on how to direct a video production process. So, it is hoped that in the future young people will be more skilled and more skilled in creating videos that are published on the YouTube channel, especially in an effort to promote the village.